Genetic architecture of obesity and related metabolic traits — recent insights from isolated populations. (June 2018) - Andersen, Mette Korre; Grarup, Niels; Moltke, Ida; Albrechtsen, Anders; Hansen, Torben
Abstract : In this mini-review, we give an overview of what is known about the genetic architecture of obesity and related metabolic traits with a primary focus on recent insights from studies of historically small and isolated populations. We start by briefly explaining what genetic architecture is and why studies of isolated populations in general are valuable if we want a complete picture of the genetic architecture of diseases and other traits among humans. Then we contrast what is known about the genetic architecture of obesity and related metabolic traits among large outbred populations, like Europeans, with results from recent studies of isolated populations. Finally, we briefly discuss the perspectives of studying isolated populations to gain insight into genetic architecture in humans.